Psychometric properties of the Maladjustment Inventory in a Spanish clinical and student sample - Jorge Osma; Alba Quilez-Orden; Jorge Ordóñez; Óscar Peris-Baquero; Enrique Echeburúa (BMC Psychology)
Abstract Background The various systems of diagnosis and classification of mental disorders underline the need to evaluate the interference caused by the different disorders in a person’s daily life. The Maladjustment Inventory (MI) evaluates the impairment in the individual’s functioning in a brief and self-applied way, through six items. The objective of this research was to explore the psychometric properties of the MI scores through two studies, one with a Spanish clinical sample (Study 1) and another with a Spanish university students’ sample (Study 2). Methods The total sample was made up of 928 participants (81.1% women, n = 495 clinical sample). Descriptive analyses, exploration of internal structure and reliability, exploratory and confirmatory factor analyses, relationship with other variables (quality of life, anxiety, depression, neuroticism and extraversion), and percentiles and T-scores were performed. Results The results showed good psychometric properties of the MI, with a good fit model for one factor solution in both samples, Cronbach’s alpha coefficient of 0.84–88, and evidence of validity based on the relationship with other variables. Conclusion The good psychometric properties of the MI, together with its brevity, make it a recommended instrument for the evaluation of interference in both clinical and research contexts.